2015
DOI: 10.2471/blt.14.150516
|View full text |Cite
|
Sign up to set email alerts
|

Eliminating artificial trans fatty acids in Argentina: estimated effects on the burden of coronary heart disease and costs

Abstract: ObjectiveTo estimate the impact of Argentine policies to reduce trans fatty acids (TFA) on coronary heart disease (CHD), disability-adjusted life years (DALYs) and associated health-care costs.MethodsWe estimated the baseline intake of TFA before 2004 to be 1.5% of total energy intake. We built a policy model including baseline intake of TFA, the oils and fats used to replace artificial TFAs, the clinical effect of reducing artificial TFAs and the costs and DALYs saved due to averted CHD events. To calculate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 29 publications
1
31
0
4
Order By: Relevance
“…After removing 723 duplicates, we screened 1084 publications by title and abstract, after which 70 full-text papers were assessed for eligibility. A total of 23 papers met the inclusion criteria (12 empirical studies 20 – 31 and 11 modelling studies; 32 42 Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After removing 723 duplicates, we screened 1084 publications by title and abstract, after which 70 full-text papers were assessed for eligibility. A total of 23 papers met the inclusion criteria (12 empirical studies 20 – 31 and 11 modelling studies; 32 42 Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on changes in lipid profile, the combined intervention was projected to avert 301 deaths, 1066 acute coronary heart disease events, 5237 DALYs and 17 million United States dollars in health-care costs annually in the adult population. 42 …”
Section: Resultsmentioning
confidence: 99%
“…However, the European Union model found that a mandatory TFA-labeling policy would not be cost-effective unless initial TFA intakes were quite high ( 43 ). For those studies that examined savings per year, health care savings ranged from US$17 million/y ( 44 ) to £230 million/y ( 39 ). Two studies ( 38 , 42 ) examined the effects of different TFA policy scenarios on different socioeconomic groups.…”
Section: Resultsmentioning
confidence: 99%
“…Two modeling studies, one in Argentina ( 44 ) and another in Denmark ( 45 ), modeled the impact of the countries' actual TFA policies, both showing positive impacts in terms of reducing CHD and CVD rates. Over the course of a 10-y period between 2004 and 2014, Argentina went from having a voluntary TFA-labeling policy to having mandatory TFA limits in foods.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the biggest contributors of TFA were meat, poultry, and fish recipes (12.47% at baseline vs. 18.75% at one year), followed by breads, rolls, biscuits, and other related products (10.75% at baseline vs. 10.70% at one year) (data not shown in table). In the United States, nutritional labelling of TFA content became mandatory in 2006 [ 37 ]. In 2007, New York City (NYC) became the first in the United States to pass a regulatory restriction on PHO use, targeting restaurants.…”
Section: Discussionmentioning
confidence: 99%